Praktik intervensi kolaboratif bagi anak berkebutuhan khusus: Studi multikasus dalam layanan pendidikan inklusif di Yogyakarta - Riski Aningrum; Annisa Annisa; Dody Bakhtiar Al-Anshori; Zykra Zakiah (Literal: Disability Studies Journal, 2026)
This study aims to analyze collaborative intervention practices in inclusive education services for children with special needs in Yogyakarta. The study employed a qualitative approach using a multi-case study design based on case reports obtained from the Disability Service Unit of Yogyakarta during the January–March 2026 period. The research data consisted of case report documents describing intervention practices, school and family support, and the developmental progress of children with diverse characteristics, including cognitive disabilities, behavioral and communication difficulties, and visual impairments. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings indicate that intervention practices in inclusive education were implemented through individualized instruction, behavioral reinforcement, self-care habituation, and coordinated support between schools and families. The forms of intervention and children’s developmental progress varied across cases depending on the characteristics of the children’s needs and the consistency of intervention practices. In several cases, the sustainability of interventions was influenced by the intensity of family involvement, particularly in implementing learning and self-care programs at home. The study also shows that collaborative practices in inclusive education are not solely related to administrative involvement among stakeholders, but are also shaped by family support capacity and the continuity of coordination between school and home environments. This study provides a contextual description of collaborative intervention practices in inclusive education based on disability service case documentation. The findings highlight the importance of strengthening service coordination, family support, and flexible interventions tailored to the individual needs of children in supporting inclusive education practices.